Improving detection of JC virus by ultrafiltration of cerebrospinal fluid before polymerase chain reaction for the diagnosis of progressive multifocal leukoencephalopathy - Nakamichi, Kazuo; Kawamoto, Michi; Ishii, Junko; Saijo, Masayuki (BMC neurology, 2019)
Progressive multifocal leukoencephalopathy (PML) is a demyelinating disorder caused by JC virus (JCV). Although detecting JCV DNA in the cerebrospinal fluid (CSF) by real-time polymerase chain reaction (PCR) is useful, diagnosis is difficult when JCV concentrations are low. We therefore aimed to lower the detection limit of real-time PCR testing by enriching JCV in the CSF via ultrafiltration. Virus suspensions and CSF specimens from 20 untreated patients with suspected PML were collected and total DNAs were extracted. The JCV large T gene was detected by quantitative real-time PCR under condition with and without prior centrifugal ultrafiltration. The JCV DNA was reliably detected to a lower limit of 10 copies/mL of virus suspension by real-time PCR with ultrafiltration. When using this method, the quantity of JCV DNA per PCR reaction increased 3.2- to 8.7-fold compared with the standard procedure. Seven patients were positive for JCV when using the standard procedure, and an additional patient was positive when using ultrafiltration. All JCV-positive patients had neurological features and magnetic resonance imaging findings compatible with PML. The detection limit of JCV DNA by real-time PCR can be lowered by viral enrichment using ultrafiltration. Our simple protocol offers a valuable tool for PML diagnosis when extremely low copy numbers of JCV are released into the CSF or when brain biopsy is not feasible.